Leveraging heterogeneous networks to analyze energy storage systems in power systems and renewable energy research: a scientometric study - Dong, Bowen; Guo, Zhen; Mulat, Aliya; Tian, Yuanhao; Lu, Mingyu; Yuan, Yixuan; Liu, Xianchen (Frontiers in Energy Research, 2024)
The transition to renewable energy sources is critical for sustainable development, yet integrating these sources into existing power systems poses significant challenges. Energy Storage Systems (ESS) are essential in enhancing the reliability and efficiency of renewable energy systems. Despite growing research, a comprehensive scientometric analysis mapping development and trends in this field is lacking. This study addresses this gap by conducting a detailed scientometric analysis of power systems and new energy research from 2014 to 2023. The novelty of this study lies in its systematic use of advanced bibliometric tools to provide a thorough analysis of the research landscape. Utilizing 425 research articles from the Web of Science database, the study employs CiteSpace to visualize academic networks, identify research hotspots, and outline current trends. Specific methodologies include burst detection to identify significant shifts in research focus, centrality measurement to determine the influence of key studies, and heterogeneous network analysis to map the interconnectedness of various research themes. The analysis reveals extensive international collaborations, with China leading in publication volume (344 articles) and centrality (0.69), followed by the USA (29 articles, centrality 0.53). Significant contributions come from institutions like North China Electric Power University,